If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (37x + 61y) + (-3x + 32y) = 0 Remove parenthesis around (37x + 61y) 37x + 61y + (-3x + 32y) = 0 Remove parenthesis around (-3x + 32y) 37x + 61y + -3x + 32y = 0 Reorder the terms: 37x + -3x + 61y + 32y = 0 Combine like terms: 37x + -3x = 34x 34x + 61y + 32y = 0 Combine like terms: 61y + 32y = 93y 34x + 93y = 0 Solving 34x + 93y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-93y' to each side of the equation. 34x + 93y + -93y = 0 + -93y Combine like terms: 93y + -93y = 0 34x + 0 = 0 + -93y 34x = 0 + -93y Remove the zero: 34x = -93y Divide each side by '34'. x = -2.735294118y Simplifying x = -2.735294118y
| 3x^2-20x-16=0 | | 1.48g-5=0.18 | | 4.8=3700 | | 6r-7=2r+18 | | -16x^2+120x+400=300 | | 65+15p=35 | | (k-3)x^2-(3k-2)x+3k+1=0 | | 3(3.8+-0.6y)+y=9 | | .05=1.82/x | | -2y=4y-42 | | 64=-2(m+7)+m | | 63+7x=84+4x | | 4x-6x=12-20-5x | | 7x/2_x=0 | | 475+40+28h=601 | | 5x-3(4x-13)=81 | | 5(3.8+-0.6y)+3y=19 | | 16=4(v+1) | | 12n-9+2n-n=-87 | | 2w^2+6=-7w | | 5x-3(-5x-9)=127 | | 40=5ln(x-2)+6 | | 2w^2+6+7w=0 | | 7.95+4.35=60 | | -3x-6(3x+14)=147 | | -6x+4-3+x=11 | | 12-3=7(n-4)+5n | | (-14)(0.22)+(-16)(0.65)=(-18)(0.13) | | 8x+7y-3x= | | -2x-2(7x-16)=-10 | | 4y+4=-2x | | 14-4X=5=X/2 |